Electrospun flexible calcium zirconate fiber membrane with excellent thermal stability and alkali resistance. Issue 9 (1st May 2022) - Yuan, Kangkang; Li, Hui; Jin, Xiaotong; Li, Chengshun; Wang, Xinqiang; Wu, Duanxi; Zhang, Guanghui
Abstract: Ceramic fibrous membranes have promising application in gas solid filtration and in areas requiring high thermal insulation, as well as catalyst supports, owing to their high porosity and low thermal conductivity. However, achieving flexible ceramic fibrous membranes that are stable at high temperatures remains a challenge. In the present work, a CaZrO3 fibrous membrane with excellent stability at 1200 °C and good flexibility at 1100 °C was achieved using a combination of sol-gel and electrospinning methods. The thermal decomposition process and microstructure evolution of CaZrO3 precursor fibers at high temperatures were discussed. The single orthorhombic phase of CaZrO3 fibers was stable up to 1400 °C. Furthermore, the CaZrO3 fibrous membrane exhibited excellent alkaline resistance. The excellent thermal stability and flexibility of the CaZrO3 fibrous membrane make it a promising candidate for high-temperature applications.